2021
DOI: 10.1007/s11854-021-0165-4
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity sequences, Kazhdan sets and group topologies on the integers

Abstract: We study the relationships between three different classes of sequences (or sets) of integers, namely rigidity sequences, Kazhdan sequences (or sets) and nullpotent sequences. We prove that rigidity sequences are non-Kazhdan and nullpotent, and that all other implications are false. In particular, we show by probabilistic means that there exist sequences of integers which are both nullpotent and Kazhdan. Moreover, using Baire category methods, we provide general criteria for a sequence of integers to be a rigi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…We now deduce topological corollaries from Theorem A, including an extension of [3,Theorem 3.8]. First, we need two definitions from [4].…”
Section: Now We Can Prove Theorem Bmentioning
confidence: 99%
See 4 more Smart Citations
“…We now deduce topological corollaries from Theorem A, including an extension of [3,Theorem 3.8]. First, we need two definitions from [4].…”
Section: Now We Can Prove Theorem Bmentioning
confidence: 99%
“…In [4], it is shown that a sequence (n k ) k∈N in Z is a TB-sequence if and only if λ n k → 1 for infinitely many λ ∈ T. By Lemma 2.7, this means that TB-sequences in Z are rigidity sequences for ergodic systems with discrete spectrum. Badea, Grivaux, and Matheron use this observation to conclude that TB-sequences are rigidity sequences (see [3,Theorem 3.8]).…”
Section: Now We Can Prove Theorem Bmentioning
confidence: 99%
See 3 more Smart Citations